An estimate of the proportion of symptomatic gonococcal, chlamydial and non-gonococcal non-chlamydial urethritis attributable to oral sex among men who have sex with men: a case–control study. (21st August 2015) - Barbee, Lindley A; Khosropour, Christine M; Dombrowski, Julia C; Manhart, Lisa E; Golden, Matthew R
Abstract : Background: Sexually transmitted infections (STIs) of the pharynx are common among men who have sex with men (MSM); the degree to which these infections are transmitted through oral sex is unknown. Methods: We conducted a case–control study of MSM attending Public Health—Seattle & King County STD Clinic between 2001 and 2013 to estimate the proportion of symptomatic urethritis cases attributable to oral sex using two methods. First, we categorised men into the following mutually exclusive behavioural categories based on their self-reported sexual history in the previous 60 days: (1) only received oral sex (IOS); (2) 100% condom usage with insertive anal sex plus oral sex (PIAI); (3) inconsistent condom usage with anal sex (UIAI); and (4) no sex. We then determined the proportion of cases in which men reported the oropharynx as their only urethral exposure (IOS and PIAI). Second, we calculated the population attributable risk per cent (PAR%) associated with oral sex using Mantel–Haenszel OR estimates. Results: Based on our behavioural categorisation method, men reported the oropharynx as their only urethral exposure in the past 60 days in 27.5% of gonococcal urethritis, 31.4% of chlamydial urethritis and 35.9% non-gonococcal, non-chlamydial urethritis (NGNCU) cases. The PAR%s for symptomatic gonococcal urethritis, chlamydial urethritis and NGNCU attributed to oropharyngeal exposure were 33.8%, 2.7% and 27.1%, respectively. Conclusions: The pharynx is an important source of gonococcal transmission, and may be important in the transmission of chlamydia and other, unidentified pathogens that cause urethritis. Efforts to increase pharyngeal gonorrhoea screening among MSM could diminish STI transmission.